Reversal of methanation-oriented to RWGS-oriented Ni/SiO2 catalysts by the exsolution of Ni2+ confined in silicalite-1 - Chen, Chia Hung; Chen, Hong Kai; Huang, Wei Hsiang; Chen, Chi Liang; Choojun, Kittisak; Sooknoi, Tawan; Tian, Hong Kang; Lin, Yu Chuan (My University, 2023)
Investigation of catalytic hydrogenation of CO2 to CO via the reverse water-gas shift (RWGS) was undertaken using Ni/SiO2-based catalysts. Among the array of catalysts tested, the Ni/SiO2 catalyst derived from the reduction of silicalite-1-encapsulated, ligand-protected Ni2+ (Ni0.2@S-1-red) exhibited promising performance. This catalyst demonstrated a CO2 conversion rate approaching the equilibrium conversion of RWGS, a selectivity for CO exceeding 99%, and a high space time yield of CO (9.7 mol gNi−1 h−1). The outcomes observed can be attributed to several factors, such as the highly dispersed Ni0 and Niδ+ species, as well as the presence of bridging oxygen of the Ni-O-Si structure, on which CO2 can be adsorbed moderately. The moderately bonded CO2 on Ni0.2@S-1-red allows for the efficient desorption of its reduced intermediate, i.e. *CO, resulting in the generation of gaseous CO at a rapid rate, consequently preventing its deep hydrogenation to CH4. Complementary Density Functional Theory (DFT) calculations were performed and revealed that CO molecules have poor adsorption and higher adsorption energy on the Ni@S-1 surface compared to the S-1 surface. This supports the rapid desorption of *CO and the observed high selectivity of CO. Moreover, the structure-activity correlation analysis further supports the claim of Ni0.2@S-1-red as a promising RWGS catalyst.